Attraction of Investment in Agriculture of Kazakhstan - Abdrakhmanova, Dinar (Asian Journal of Agriculture and Rural Development, 2013)
Characteristic for conditions competition increase in the market of the investments, interfaced to world financial crisis, makes superrigid deman ds to investment decisions. In similar conditions the exit on the capital markets is one of the key advantages, providing to the enterprises their further development. Attraction of investments is interfaced to a number of difficulties. In connection with shortage of own means for financing of investment activity of the organizations by the basic source of financing there was an extra financing. Necessity of considerable volume of financial resources on development of investment projects does their attraction by a paramount problem of the enterprises-borrowers. Availability of credit sources of financing is limited both because of the high price of the extra capital, and owing to inability of the enterprises-borrowers to interest potential creditors in realization of investment projects. It causes necessity of an economic justification of efficiency and appeal of investment investments. Only having defined, what concrete parameters the company should possess, and having developed concrete ways and indicators of achievement of these parameters, it is possible in modern conditions effectively to develop business. Such aspiration creates investment appeal and is realized by means of basic tools considered in given work.